IMPROVING STUDENTS WRITING SKILL BY COLLABORATIVE WRITING FOR STUDENTS OF XI IPA 2 IN SMA NEGERI 4 KEDIRI - Jawari Muslim; Galuh Nur Rohmah (Wiralodra English Journal, 2022)
Studies on collaborative writing have proven its effectiveness for improving student's writing performance. However, further exploration is needed on how this method is applied to different writing genres. This research attempts to investigate the result of students’ writing ability by using of collaborative writing. It also describes the implementation as well as the students’ response in using this technique. The subjects were the eleventh graders of SMAN 4 Kediri. The type of this research is a classroom action research. There were two cycles, each of which consisted of three meetings and ended with post-test to measure the improvement of the students’ writing ability. The data were collected by using observation lists, questionnaire, documentation, and writing test. The result showed that all of the students had passed the passing grade. In addition, they stated that they felt happy during the process of writing collaboratively as it was easier for them to compose a text collaboratively with their friends. The finding implied that writing teacher should focus on teaching and learning strategies not only focusing on the transfer of writing concepts. Therefore, collaborative narrative writing is an appropriate technique to be used in improving the students’ writing ability.